The word-forming morphonology of borrowed verbs derived from nouns (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with the process of word-forming of borrowed verbs. The morphonological features of word-formative morphemes are described. The analysis of morphonological phenomena is given. The morphonological models and morphonological classes of derived verbs are established.
Keywords: derived verbs; morphonological phenomena; morphonological models; morphonological classes